Experimental Investigation on Velocity Field in Subterranean Water Flow Under Different Size of Gravel (Journal of Environmental Science Studies, 2024)
Direct measurement of flow velocities within subterranean layer is important for predicting subterranean flow. The authors conducted a study on the velocity field of subterranean water flow by directly measuring the flow velocity within the subterranean layer using crushed stone to form a gravel mount. Namely, they directly measured subterranean flow velocities for five different sizes of gravels (5.3 mm, 16.5 mm, 25.5 mm, 47.5 mm, and 92.4 mm) and showed for the first time how the time-averaged flow velocity and standard deviation vary with the size of the gravels. The velocity field including turbulent intensity in the subterranean layer was revealed, and the flow field of the subterranean flow depends on the size of the gravels that make up the gravel mount. The relationship between the configuration of the gravel mount, the water surface profile, and the velocity field within the subterranean layer allowed a discussion of the vertical distribution of time-averaged velocities and standard deviations, as well as stream wise changes in the subterranean layer. From the results of time-averaged velocity and turbulent intensity (here, standard deviation) in the subterranean layer for different sizes of gravels, it is possible to estimate the velocity field of subterranean water flow formed by the grain size distribution of the depositing gravels and the difference in water level. In other words, by clarifying the velocity field of subterranean water flow consisting of different gravel sizes, it may be possible to evaluate the subterranean function of the sand and gravel zone deposited by transported gravels.